2023
DOI: 10.1007/s10530-023-03113-4
|View full text |Cite
|
Sign up to set email alerts
|

No evidence of a long-lived seedbank in common buckthorn, Rhamnus cathartica L., within Minnesota deciduous forests

Abstract: The persistence of invasive plant species in soil seedbanks can pose a significant obstacle to effectively managing invasive plant populations. Rhamnus cathartica (common buckthorn, hereafter 'buckthorn') is a wide-spread invader of forest understories in North America that can quickly re-establish following removal, in part due to germination of buckthorn seedbanks. Although empirical evidence seems slight, influential organizations communicate that buckthorn seedbanks endure for at least six years. In order … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Firstly, although a higher density of F. alnus was found near forest roads, there still are patches of F. alnus inside the forest or hard-to-access areas where field surveyors generally do not check. Finding and managing such remote populations of F. alnus would prevent the spread and re-invasion of F. alnus after a successful control [19]. Current drone technologies including sensors and high-resolution satellite imagery could help find F. alnus located remotely or in hard-to-access areas [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Firstly, although a higher density of F. alnus was found near forest roads, there still are patches of F. alnus inside the forest or hard-to-access areas where field surveyors generally do not check. Finding and managing such remote populations of F. alnus would prevent the spread and re-invasion of F. alnus after a successful control [19]. Current drone technologies including sensors and high-resolution satellite imagery could help find F. alnus located remotely or in hard-to-access areas [21].…”
Section: Discussionmentioning
confidence: 99%
“…Herbicide treatment of girdled stems and cut stumps, prescribed burns followed by foliar herbicide, and the removal of roots from cut areas also can be used to control F. alnus [18]. Previous studies [17,19] also suggested the complete removal of F. alnus for initial 2-year management to prevent its reinvasion. In the Allegheny National Forest, foliar herbicides (e.g., glyphosate), pre-emergent herbicides (e.g., sulfometuron methyl), and manual cutting or mastication are used to control F. alnus [20].…”
Section: Introductionmentioning
confidence: 99%